2023
DOI: 10.1186/s12872-023-03572-6
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil to lymphocyte ratio (NLR) prognostic effects on heart failure; a systematic review and meta-analysis

Mehrbod Vakhshoori,
Sepehr Nemati,
Sadeq Sabouhi
et al.

Abstract: Background Neutrophil to lymphocyte ratio (NLR), as a recent inflammatory index, has been reported to be a prognostic tool in different diseases. However, implication of this ratio in heart failure (HF) is less investigated. In this systematic review and meta-analysis, we aimed to assess the potential impact of NLR on HF clinical outcomes. Methods Relevant English published records in PubMed, Scopus, Embase, and Web of Science were screened up to J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…Neutrophil-to-lymphocyte ratio (NLR) has been investigated as a recent inflammatory index and a prognostic tool in HF during the last few years. It is a simple prognostic tool for risk stratification and prioritizing high risk patients in clinical settings, especially in resource-limited nations [ 110 ]. In a recent meta-analysis [ 110 ], it was found that mean NLR in HF patients was 4.38 (95% CI: 4.02–4.73).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neutrophil-to-lymphocyte ratio (NLR) has been investigated as a recent inflammatory index and a prognostic tool in HF during the last few years. It is a simple prognostic tool for risk stratification and prioritizing high risk patients in clinical settings, especially in resource-limited nations [ 110 ]. In a recent meta-analysis [ 110 ], it was found that mean NLR in HF patients was 4.38 (95% CI: 4.02–4.73).…”
Section: Discussionmentioning
confidence: 99%
“…It is a simple prognostic tool for risk stratification and prioritizing high risk patients in clinical settings, especially in resource-limited nations [ 110 ]. In a recent meta-analysis [ 110 ], it was found that mean NLR in HF patients was 4.38 (95% CI: 4.02–4.73). Each unit increase in this biomarker has been associated with an increased mortality risk of 1.12 (95% CI: 1.02–1.23, p = 0.013) times, and this risk was higher among patients with higher NLR values than proposed cut-offs (HR: 1.77, 95% CI: 1.27–2.46, p = 0.001); being in a higher NLR tertile was associated with increased death likelihood (T2 vs. T1: HR: 1.56, 95% CI: 1.21–2.00, p = 0.001, T3 vs. T1: HR: 2.49, 95% CI: 1.85–3.35, p < 0.001) [ 110 ]; and NLR could be considered as a biomarker that mirrors the balance between acute and chronic inflammation and adaptive immunity, as well as a robust prognostic marker of disease severity and predictor of mortality in several diseases, including sepsis, pneumonia, COVID-19, cancer and cardiovascular diseases [ 111 ].…”
Section: Discussionmentioning
confidence: 99%